Improvement of gasification performance of Eucalyptus globulus stumps with torrefaction and densification pre-treatments. (15th October 2017) - Pinto, Filomena; Gominho, Jorge; André, Rui Neto; Gonçalves, David; Miranda, Miguel; Varela, Francisco; Neves, Diogo; Santos, João; Lourenço, Ana; Pereira, Helena
Highlights: Gasification of eucalypt stumps. Study of the biomass pre-treatments: densification, torrefaction and densification of torrefied feedstock. Effect of biomass pre-treatments on syngas yield and quality. Effect of biomass pre-treatments on the release of H2 S and NH3. Selection of the best biomass pre-treatments to improve gasification performance and syngas composition. Abstract: Eucalyptus globulus stumps has been used as biofuel for energy production. However, forest biomass presents some disadvantages (high moisture, volatiles and oxygen contents, hydrophilic nature, low calorific value, bulk density and energy density). To overcome this, torrefaction and pelletisation were tested. Based on the assays, 250 °C and 30 min were selected as the best conditions for the torrefaction. The summative chemical analysis has shown that torrefied stumps presented higher total extractives and lignin content and lower monosaccharides in relation to raw stumps. Eucalyptus stumps were also densified to produce pellets of raw and torrefied material. The materials obtained by the different pre-treatments studied were gasified in a fluidised bed reactor. Gasification gas obtained with raw stumps was compared to those obtained with pre-treated stumps by pelletisation (or densification), torrefaction and torrefaction followed by pelletisation. The results obtained showed that bio-syngas was improved when torrefied biomass was used, as there was an increase in gas yield and CGE (Cold Gas Efficiency) and lower tar were produced. The best pre-treatment for eucalyptus stumps was densification after torrefaction, as at 850 °C, gas yield was about 1.22 Nl/g daf and CGE was around 65%. This syngas contained around 38% of H2, 27% of both CO and CO2 and 5% of CH4 .